2017
DOI: 10.1111/1440-1681.12817
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitric oxide on large‐conductance Ca2+‐activated K+ currents in human cardiac fibroblasts through PKA and PKG‐related pathways

Abstract: The human cardiac fibroblast (HCF) is the most abundant cell type in the myocardium, and HCFs play critical roles in maintaining normal cardiac function. However, unlike cardiomyocytes, the electrophysiology of HCFs is not well established. In the cardiovascular system, Ca -activated K (KCa) channels have distinct physiological and pathological functions, and nitric oxide (NO) plays a key role. In this study, we investigated the potential effects of NO on KCa channels in HCFs. We recorded strong oscillating, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…These results indicate that NO (100 µM SNAP) increased I K of HCFs through AC/cAMP/PKA signaling mechanisms. It has been reported that NO also modulates cardiac IBK Ca channels, which are also important K + channels in HCFs [ 13 ], and Na + channels in guinea pig and mouse ventricular myocytes through the cAMP and cGMP pathways [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results indicate that NO (100 µM SNAP) increased I K of HCFs through AC/cAMP/PKA signaling mechanisms. It has been reported that NO also modulates cardiac IBK Ca channels, which are also important K + channels in HCFs [ 13 ], and Na + channels in guinea pig and mouse ventricular myocytes through the cAMP and cGMP pathways [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Commercially available primary adult human ventricular cardiac fibroblasts (HCF-av, Catalogue #6310 from ScienCell, Carisbad, CA, USA) were used. These cells were used for many bimolecular and electrophysiological experiments [ 3 , 13 , 40 , 56 , 57 , 58 ] and confirmed as fibroblasts by discoidin domain receptor 2 staining [ 58 ]. The cells were cultured in Dulbecco’s modified eagle’s medium (DMEM; Welgene, Gyeongsan, Gyeongsangbuk-do, Korea) that was supplemented with fetal bovine serum (10%, Welgene) and a penicillin-streptomycin solution (100×; GenDEPOT, Barker, TX, USA) in a humidified atmosphere of 5% CO 2 and 95% air at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of NO to the heme group of sGC leads to increased conversion of GTP to cGMP, which in turn activates PKG. The cGMP signaling pathway are the main mechanisms for mediating the effects of NO on IBK in HCFs [25]. Therefore, we assessed the effects of cGMP on IBK of HCFs.…”
Section: Effect Of Cgmp Signaling Pathway On Co-induced Ibk Activation In Hcfsmentioning
confidence: 99%
“…The large-conductance Ca 2+ -activated K + (BK) channel is the main K + channel in HCFs [22,25]. The BK channel contributes to the resting membrane potential of cardiac fibroblasts [26] and the electrical coupling of cardiomyocytes-fibroblasts [23].…”
Section: Introductionmentioning
confidence: 99%